2015
DOI: 10.2147/ijn.s88514
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles induce heme oxygenase-1 expression through Nrf2 activation and Bach1 export in human vascular endothelial cells

Abstract: It has been reported that increased levels and activity of the heme oxygenase-1 (HO-1) protein ameliorate tissue injuries. In the present study, we investigated the effects and mechanisms of action of gold nanoparticles (AuNPs) on HO-1 protein expression in human vascular endothelial cells (ECs). The AuNPs induced HO-1 protein and mRNA expression in a concentration- and time-dependent manner. The induction was reduced by the thiol-containing antioxidants, including N-acetylcysteine and glutathione, but not by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 48 publications
(65 reference statements)
1
7
0
Order By: Relevance
“…The cell lysates were prepared as previously described [24]. The total proteins were analyzed by electrophoresis, blotted onto PVDF membranes, and then probed using an Ab raised against the indicated protein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell lysates were prepared as previously described [24]. The total proteins were analyzed by electrophoresis, blotted onto PVDF membranes, and then probed using an Ab raised against the indicated protein.…”
Section: Methodsmentioning
confidence: 99%
“…Oligonucleotide polymerase chain reaction (PCR) primers targeting human collagen, CTGF, HSP47, and β-actin were synthesized (Table 1). The total RNA extraction, reverse transcription of total RNA to cDNA, and PCR analysis have been previously described [24]. The PCR was performed with 30 cycles of denaturation at 94°C for 1 min, annealing at 52°C for 1 min, and elongation at 72°C for 1.5 min on the ABI 7200 Thermal Cycler (Applied Biosystems, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, gold colloids have been thought to cure various diseases for many centuries, and recent studies have demonstrated that this effect is mediated by inhibition of NF-B activation 10 . Different studies showed a similar effect in the case of Au NPs in vitro and in vivo, this effect being usually mediated by antioxidant properties 11,12,13,14,15 . However, other studies showed opposite results.…”
Section: Discussionmentioning
confidence: 71%
“…Gold (Au) can be deposited as nanoparticles (NPs) smaller than 10 nm in diameter on a variety of metal oxide (MOx) NPs. Au/MOx NPs have attracted much attention due to their high catalytic performance for such as room temperature CO oxidation and selective oxidations in liquid phase 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that AuNp may be involved in regulating the KEAP1 (Kelch ECH-associated protein 1)-NRF2 (nuclear factor erythroid 2-related factor 2) pathway, and adjusting the cytoprotective response to endogenous and exogenous stress caused by reactive oxygen species (ROS) [46]. Under baseline conditions, the KEAP1 repressor protein binds to the inactive NRF2 factor present in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%